2005
DOI: 10.1128/cmr.18.1.217-245.2005
|View full text |Cite
|
Sign up to set email alerts
|

Update on Human Herpesvirus 6 Biology, Clinical Features, and Therapy

Abstract: Human herpesvirus 6 (HHV-6) is a betaherpesvirus that is closely related to human cytomegalovirus. It was discovered in 1986, and HHV-6 literature has expanded considerably in the past 10 years. We here present an up-to-date and complete overview of the recent developments concerning HHV-6 biological features, clinical associations, and therapeutic approaches. HHV-6 gene expression regulation and gene products have been systematically characterized, and the multiple interactions between HHV-6 and the host immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
441
2
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(473 citation statements)
references
References 450 publications
6
441
2
12
Order By: Relevance
“…21 Human herpes virus 6 was discovered in 1986 and two subtypes can be found, type A and type B. HHV6-B is extremely widespread in the population and infects almost all children within the first few years of life establishing latency after primary infection. 22 As expected, none of the cord blood used in this study showed HHV6 positivity 23 and all HHV6 infections were because of the type B virus. 22 Thus, we postulate that HHV6 originates from the reactivation of endogenous HHV6.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…21 Human herpes virus 6 was discovered in 1986 and two subtypes can be found, type A and type B. HHV6-B is extremely widespread in the population and infects almost all children within the first few years of life establishing latency after primary infection. 22 As expected, none of the cord blood used in this study showed HHV6 positivity 23 and all HHV6 infections were because of the type B virus. 22 Thus, we postulate that HHV6 originates from the reactivation of endogenous HHV6.…”
Section: Discussionmentioning
confidence: 88%
“…22 As expected, none of the cord blood used in this study showed HHV6 positivity 23 and all HHV6 infections were because of the type B virus. 22 Thus, we postulate that HHV6 originates from the reactivation of endogenous HHV6. Compared with MUD, in which the results were in the range of most reported studies, 22,24,25 CBT showed a significant by higher incidence and an higher median viral load of HHV6 infections and for a longer period of time after transplant.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To date, only broad-spectrum and relatively toxic antiherpes virus drugs (for example, (val)ganciclovir and foscarnet-sodium) are used in the treatment of HHV6 disease or -reactivation. 8,9 With the progress in molecular diagnostics, better monitoring allows for further elucidation of the role of HHV6 reactivation and therapeutic protocols after HSCT. Therefore, we studied the predictors for HHV6 reactivation and the association of HHV6 reactivation with clinical outcome in adult allogeneic-HSCT recipients.…”
mentioning
confidence: 99%
“…Human herpesvirus-6 (HHV-6) is a ubiquitous virus which is widespread throughout the world [1]. Two major subgroups of HHV-6 have been identified, variants A and B, of which variant B is the most common.…”
mentioning
confidence: 99%